Analysis of the 1988 Greenhouse Novel by Pramoedya Ananta Toer with a Postcolonial Approach - Chaniago, Fitri Handayani; Sinaga, Shafira Rahma Dina; Turnip, Putri Firmawindy; Simatupang, Alzyra Fatiha; Lubis, Fitriani (Indonesian Journal of Advanced Research, 2024)
The novel "Rumah Kaca" by Pramoedya Ananta Toer is a literary work that depicts the complexity of the relationship between Dutch colonialism and Indonesian society during the colonial period. With a postcolonialism approach, this analysis explains how this novel shows the impact and legacy of colonialism on the daily life, politics, and identity of the Indonesian nation. Through powerful characters and stories, Pramoedya depicts the struggles and conflicts faced by indigenous peoples in opposing colonial oppression, as well as their efforts to maintain their cultural identity and local values. Thus, the novel "Rumah Kaca" is not only an alluring literary work, but also a source of inspiration and a deep understanding of the struggle of the Indonesian people in facing and overcoming the period of colonialism.